2009
DOI: 10.1590/s1807-59322009000700004
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Depressive Symptoms by Physicians

Abstract: OBJECTIVE:To investigate the recognition of depressive symptoms of major depressive disorder (MDD) by general practitioners.INTRODUCTION:MDD is underdiagnosed in medical settings, possibly because of difficulties in the recognition of specific depressive symptoms.METHODS:A cross-sectional study of 316 outpatients at their first visit to a teaching general hospital. We evaluated the performance of 19 general practitioners using Primary Care Evaluation of Mental Disorders (PRIME-MD) to detect depressive symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
1
14
1
1
Order By: Relevance
“…This finding is in contrast to others (Bech et al, 2009) who have not found that change in appetite, as measured by the HAMD-17, is sensitive to response. Despite the possibility that this is a chance finding, it is also possible that early changes in somatic symptoms (gastrointestinal) may be linked to antidepressant treatment outcome, which is consistent with studies suggesting a relationship between somatic symptoms and depression (Henriques et al, 2009; Mussell, et al, 2008; Trivedi, 2004). Additionally, there is evidence that change in appetite is suggestive of relapse and improvement in treatment (Kanai et al, 2003; Trivedi, 2004).…”
Section: Discussionsupporting
confidence: 77%
“…This finding is in contrast to others (Bech et al, 2009) who have not found that change in appetite, as measured by the HAMD-17, is sensitive to response. Despite the possibility that this is a chance finding, it is also possible that early changes in somatic symptoms (gastrointestinal) may be linked to antidepressant treatment outcome, which is consistent with studies suggesting a relationship between somatic symptoms and depression (Henriques et al, 2009; Mussell, et al, 2008; Trivedi, 2004). Additionally, there is evidence that change in appetite is suggestive of relapse and improvement in treatment (Kanai et al, 2003; Trivedi, 2004).…”
Section: Discussionsupporting
confidence: 77%
“…A study seeking to identify depressive symptoms in the elderly in the general outpatient setting of the Hospital das Clínicas, in São Paulo (Brazil), concluded that the presence of comorbidities may decrease the sensitivity of physicians to specific symptoms of depression, causing them to consider the symptoms as psychological reactions resulting from other diseases (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Financial support is important, but care for the elderly with depressive symptoms also includes listening, observation, care and support whenever needed. Understanding the functioning of the elderly with depression can subsidize planning of care in order to meet their social and health needs (4,13) .…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, clinical presentations may include the presence of painful (PSSs) as well as nonpainful somatic symptoms (NPSSs) 1. Nonetheless, somatic symptoms in the course of MDE often go underestimated2 despite their impact on the course of illness and treatment choices. In fact, when inappropriately recognized and treated, (medically unexplained) somatic symptoms – considered as symptoms otherwise not referable to nonpsychiatric disturbances – are associated with poor prognosis, higher risk for residual symptomatology, as well as increased risk for relapse and recurrence 36.…”
Section: Introductionmentioning
confidence: 99%